Avaliação das principais alterações metabólicas com uso de nutrição parenteral em crianças e adolescentes de uma unidade pediátrica hospitalar - Eliana Ferreira da Silva (2024)
INTRODUCTION: Parenteral nutrition (PN) consists of the intravenous administration of an emulsion composed of water, glucose, amino acids, lipids, vitamins and minerals, in order to provide nutrients to maintaining body function and adequate growth, which is greater during the phase from childhood to adolescence. Since nutrients are delivered directly into the bloodstream by an intravenous access device, complications become more frequent when comparing PN to other nutritional routes. Patients using parenteral nutrition need to be evaluated in a global and constant way, requiring monitoring of complications arising from processes of metabolic, technical or infectious origin. The present study aims to demonstrate the importance of monitoring patients on PN, facilitating the identification of factors that make patients more likely to develop these changes, which will allow for more rigorous monitoring and seek to reduce child morbidity and mortality in these cases. OBJECTIVES: The present study aimed to evaluate the main metabolic changes that occurred during the use of parenteral nutrition in children and adolescents being monitored at the Pediatrics Inpatient Unit of Hospital das Clínicas da UFMG (HCUFMG/Ebserh) during the period from 2012 to 2022. METHODS: Cross-sectional, observational study, with an initial retrospective phase and prospective follow up of patients using PN. Information was compiled from standardized care records for patients receiving nutritional support, information from medical records and data from the hospital's laboratory test results system. RESULTS: A total of 193 patients were evaluated, 56% of whom were male and the most prevalent age group was 0 to 1 year, with a median of 3 years. During the period evaluated, 56% of patients presented some type of metabolic alteration, with PN related liver disease being the most prevalent finding, representing 38% of complications. Regarding the profile of the predominant underlying diseases, 39% of patients had gastrointestinal disease. This group had the highest prevalence of metabolic changes (43%), with a statistically significant difference in the prevalence of hyperglycemia in this group when compared to the others (p=0.01), with no difference in relation to other complications. CONCLUSION: The results of the present study made it possible to identify that despite the benefits that PN brings, the majority of patients present some type of metabolic alteration, and it is therefore important to ensure clinical and laboratory monitoring during the use of PN and carry out interventions to minimize metabolic complications caused by the use of PN, especially in patients with diagnoses related to the gastrointestinal tract.